2022
DOI: 10.1038/s41419-022-04521-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oral administration of an HNF4α agonist prevents weight gain and hepatic steatosis by promoting increased mitochondrial mass and function

Abstract: We report here that the potent HNF4α agonist N-trans-caffeoyltyramine (NCT) promotes weight loss by inducing an increase in mitochondrial mass and function, including fatty acid oxidation. Previously, we found in a short term trial in obese mice that NCT promoted reversal of hepatic steatosis through a mechanism involving the stimulation of lipophagy by dihydroceramides. NCT led to increased dihydroceramide levels by inhibiting dihydroceramide conversion to ceramides. Here, we were able to administer NCT orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Current data on NCT and NFT indicate that its role as an HNF4α agonist can affect many organs and organ systems. The data presented in this contribution show that NCT, and, to a lesser extent, The current body of literature demonstrates NCT and NFT's role in liver health and lipid flux within the liver, as well as gut health (Veeriah et al, 2022). Previous work has demonstrated a role for NCT and NFT in gut barrier function due to its HNF4αagonist properties.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Current data on NCT and NFT indicate that its role as an HNF4α agonist can affect many organs and organ systems. The data presented in this contribution show that NCT, and, to a lesser extent, The current body of literature demonstrates NCT and NFT's role in liver health and lipid flux within the liver, as well as gut health (Veeriah et al, 2022). Previous work has demonstrated a role for NCT and NFT in gut barrier function due to its HNF4αagonist properties.…”
Section: Resultsmentioning
confidence: 65%
“…While the aforementioned data have been generated in pre-clinical studies, it shows proof of concept and provides the basis for further clinical investigation of NCT and gut health. In cell The phenomena noted in cell culture above have been reproduced in obese mice upon administeration of NCT for 10 weeks (Veeriah et al, 2022). What is notable about this study, is that the mice were administered NCT orally, which simulates dietary intake of NCT.…”
Section: Introductionmentioning
confidence: 72%
“…Consequentially, loss of Hnf4 increases carbohydrate dependence and impairs mitochondrial β‐oxidation, rendering fatty acid transport into the mitochondria deficient (Barry & Thummel, 2016 ; Palanker et al., 2009 ). Interestingly, it has been reported that administration of an Hnf4 agonist in conjunction with a HFD led to marked increases in mitochondrial mass, along with increased expression of mitochondrial ETC proteins in mice (Veeriah et al., 2022 ). Additionally, it has been reported that Hnf4 protects against ROS production (Darsigny et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Food quality scoring systems that aim to capture elements of the food matrix, including degree of processing, relative ratios of nutrients, and missing bioactives, are being developed [ [29] , [30] , [31] ]. Commercial efforts are starting to provide complementary solutions to nutritional guidance such as smart phone applications to personalize and prioritize the whole food selection as well as next-generation products that reincorporate bioactive ingredients into functional foods [ [32] , [33] , [34] , [35] , [36] , [37] ].…”
Section: St-century Nutrition – Bioactives and Filling The Food Gapsmentioning
confidence: 99%